Health-economic analysis of tocilizumab in patients with rheumatoid arthritis and systemic juvenile arthritis - A. S. Kolbin; A. A. Kurylev; S. A. Mishinova; Yu. E. Balykina; M. A. Proskurin (Izdatelstvo OKI, 2020)
Rationale. Rheumatoid arthritis (RA) and systemic juvenile arthritis (sJA) are the most frequent rheumatic diseases in adults and adolescents, consequently. Biologics disease modifying antirheumatic drugs (bDMARDs) are eff ective in treatment of RA and s JA. Aim. To perform health-economic analysis of tocilizumab for subcutaneous and intravenous injections in patients with RA and sJA comparing to TNF-α inhibitors. Materials and methods. Cost-minimizing analysis was used from the perspective of healthcare system (accounting for direct medical costs) with the modelling horizon - 1 year. We included into the model cost of RA and sJA bDMARDs, cost of adverse events correction and costs of laboratory and instrumental diagnostic. Results. Cost minimizing ratio of tocilizumab (subcutaneous form) in RA patients comparing to adalimumab (Humira), сertolizumab pegol, golimumab were 111 536; 129 094; 85 244 RUR, consequently favour to tocilizumab. Tocilizumab was less costly comparing to adalimumab (Humira), certolizumab pegol, golimumab by 12.8, 14.5, 10,0 %, consequently. Cost minimizing ratio of tocilizumab in RA patients comparing to adalimumab (Dalibra), etanercept, infl iximab (Remicade) were 40 497; 54 355; 28 419 RUR in favour to comparators. Tocilizumab was more costly comparing to adalimumab (Dalibra) etanercept, infl iximab (Remicade) by 5.6; 7.7; 3.9 %, consequently. Cost minimizing ratio of tocilizumab in sJA patients comparing to kanakinumab, adalimumab (Humira) and adalimumab (Dalibra) were 6 535 234; 478 297 and 323 263 RUR. Tocilizumab was less costly comparing to kanakinumab, adalimumab (Humira) and adalimumab (Dalibra) by 93.3; 50.6 and 41.1 %, consequently. Conclusions. Tocilizumab is economically reasonable comparing to others TNF-α inhibitors in patients with RA and sJA.